1996
DOI: 10.1095/biolreprod54.1.208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hormones and protein kinase inhibitors on expression of steroidogenic enzyme promoters in electroporated primary rat granulosa cells

Abstract: Previous studies have shown that inhibitors of protein tyrosine kinases, tyrphostins, can markedly attenuate the steady-state levels of mRNAs of hormone-induced genes expressed in ovarian cells. To further elucidate the mechanism of tyrphostin action, rat granulosa cells were electroporated with chimeric expression vectors containing the promoters of two key steroidogenic genes, cholesterol side chain cleavage cytochrome P450 (CYP11A; P450scc) and aromatase cytochrome P450 (CYP19; P450arom), ligated to the CAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Specifically, we have shown that LH rapidly, but transiently, induces PR mRNA and protein in FSH/Tdifferentiated (preovulatory) granulosa cells in culture (10). Although these differentiated cells provide the most physiological model in which to conduct transfection assays with PR promoter-reporter constructs, they do not transfect easily or efficiently (21). Therefore, to determine the efficacy of using immature granulosa cells as a model for analyzing PR promoterreporter constructs, it was necessary to determine whether the endogenous PR gene could be activated in these cells, if given the appropriate stimulus.…”
Section: Induction Of Pr Mrna In Cultured Granulosa Cellsmentioning
confidence: 99%
“…Specifically, we have shown that LH rapidly, but transiently, induces PR mRNA and protein in FSH/Tdifferentiated (preovulatory) granulosa cells in culture (10). Although these differentiated cells provide the most physiological model in which to conduct transfection assays with PR promoter-reporter constructs, they do not transfect easily or efficiently (21). Therefore, to determine the efficacy of using immature granulosa cells as a model for analyzing PR promoterreporter constructs, it was necessary to determine whether the endogenous PR gene could be activated in these cells, if given the appropriate stimulus.…”
Section: Induction Of Pr Mrna In Cultured Granulosa Cellsmentioning
confidence: 99%
“…To understand the mechanism of the cAMP-PKA signal on the promoter activity of CYP11A1, the regulatory elements in its promoter have been analyzed in bovine CYP11A [1,23], rat CYP11A [28], mouse Cyp11a [2,21], and human CYP11A1 [3,16,39,40]. These investigations have identified certain cisacting elements conferring cAMP responsiveness via interactions with their specific transcription factors, using standard methods for the analysis of regulatory interacting proteins [29].…”
Section: Cyp11a1 Promoter Activity Regulated By Camp Signalingmentioning
confidence: 99%
“…Various reports have directly implicated tyrosine kinase pathways in ovarian steroidogenesis. Addition of specific tyrosine kinase inhibitors to cultured rat granulosa cells results in inhibition of LH-stimulated progesterone production and Cyp11a1 mRNA expression [57][58][59]. Other studies have shown synergistic effects of insulin or IGF1 on gonadotropin-stimulated progesterone production and expression of Cyp11a1 and Hsd3b mRNAs by rat and human granulosa cells [3,4,8].…”
Section: Discussionmentioning
confidence: 96%